Publishing journal articles a scientific guide for new authors worldwide - Yan, Zheng 1958- (Cambridge University Press, 2021)
"Journal publication and grant writing are two core professional skills for new scholars today. However, systematic training is not typically offered in graduate programs worldwide. This book equips readers with the current scientific knowledge by providing a concise introduction to the science of journal article publication. The overall structure generally matches the curriculum of a graduate course and each chapter features a learning sequence based on Daniel Kahneman's intuitive judgement theory. The volume analyzes the intuitive thoughts of new authors from a variety of countries, uses over 50 real-life cases, and focuses on core concepts from nearly 100 research articles. It provides scientific advice for new authors, junior researchers, and graduate students to publish their scholarly work and advance their academic careers. Zheng Yan graduated from Harvard University Graduate School of Education and is now Associate Professor of Developmental and Educational Psychology at University at Albany. He is also the funding editor-in-chief of Human Behavior and Emerging Technologies. His research focuses on answering the basic question of how modern humans live with emerging technologies"--
Keywords: Wissenschaftlicher Nachwuchs; Veröffentlichung; Zeitschriftenaufsatz; Academic writing; Scholarly publishing; Proposal writing for grants